The impact of mass customization products on consumer needs / Afiqah Abdullah - Abdullah, Afiqah (2014)
Mass customization as one of the popular business strategies in designed to simultaneously compete on two important competitive priorities, which is the price and customization level of a product itself Mass customization is a unique strategy whose implement the promises with the customers in all four of the competitive priorities - price, quality, flexibility, and speed at the same time. Mass customized goods are goods produced to the design specifications 0 f individual customer (Bendapudi and leone 2003; Liechty, Venkaatram, and Cohen 2001; Piller 2003). Understanding the individual differences in attitudes toward mass customization goods is important for two reasons. First, mass customization trends are becoming more productive in consumer markets nowadays. So, while mass customization programs may offer great potential for consumer product marketers, the strategy is not a sure thing. To identify individual characteristics that drive attitudes toward mass customized goods may provide insight into market conditions in which mass customization trends will succeed and those in which they may fail.